2020
DOI: 10.1186/s12875-020-01211-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control in patients with a previous stroke/transient ischaemic attack in primary care in Ireland: a cross sectional study

Abstract: Background Uncontrolled blood pressure (BP) is an important modifiable risk factor for recurrent stroke. Secondary prevention measures when implemented can reduce stroke re-occurrence by 80%. However, hypertension control rates remain sub-optimal, and little data is available from primary care where most management occurs. The aim of this study was to describe BP control in primary care-based patients with a previous stroke or transient ischaemic attack (TIA) in Ireland, and to concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…However, despite the broad availability of lifestyle interventions and drug treatment, BP targets are met in merely 28.4 to 38.8% in general cohort of hypertensive patients [2,7,8]. Similar rates were reported in particular subgroups, such as patients with a history of coronary artery disease or stroke [9,10]. However, no dedicated prospectively gathered data are available on the adequacy of BP control in a more heterogeneous, real-world cohort of high-risk patients as defined per-and treated according to contemporary guidelines [2,11].…”
Section: Introductionmentioning
confidence: 84%
“…However, despite the broad availability of lifestyle interventions and drug treatment, BP targets are met in merely 28.4 to 38.8% in general cohort of hypertensive patients [2,7,8]. Similar rates were reported in particular subgroups, such as patients with a history of coronary artery disease or stroke [9,10]. However, no dedicated prospectively gathered data are available on the adequacy of BP control in a more heterogeneous, real-world cohort of high-risk patients as defined per-and treated according to contemporary guidelines [2,11].…”
Section: Introductionmentioning
confidence: 84%
“…General practices in counties Limerick and Clare, in the mid-west of Ireland, who had taken part in a recent cross-sectional survey of stroke and TIA [8] were invited to take part in the feasibility study. All practices used electronic medical records (EMRs) and cared for both public (funded through the Primary Care Reimbursement Service (PCRS) scheme [16]) and private (fee-paying) patients.…”
Section: Participantsmentioning
confidence: 99%
“…A survey of secondary prevention of stroke in Europe has shown that satisfactory levels of blood pressure control were found in less than 60% of countries [7]. A recent cross-sectional survey in Irish General Practice [8] demonstrated that one-third of patients did not have their blood pressure adequately controlled. The reasons for sub-optimal BP control are multi-faceted.…”
Section: Introductionmentioning
confidence: 99%
“…For now, in light of the evidence described above, a target systolic BP of <130 mm Hg should apply to the vast majority of patients after TIA/stroke, except in severe intracranial atherosclerotic stenosis where a slightly more liberal target of <140 mm Hg is recommended. [60][61][62] Given that only a third of patients even achieve a BP of 130/80 mm Hg after stroke, [14][15][16] considerations of over-treatment in select patient groups should not deter pursuit of tight BP control.…”
Section: (Sps3 [Secondary Prevention Of Small Subcortical Strokes Tri...mentioning
confidence: 99%
“…[7][8][9] Randomized trials have established that lowering BP reduces this risk, 10 but long-term BP control after stroke in practice remains poor, due in part to widespread under-treatment and under-adherence. [11][12][13] Only a third of patients achieve guideline BP targets [14][15][16] and over 20% discontinue their antihypertensive drugs within the first year after stroke. 17 A lack of clarity surrounding best practice for assessment and control of BP in secondary prevention of stroke might be a contributing factor to inadequate BP management in current practice.…”
mentioning
confidence: 99%